Nutrient management in organic farming of cucumber (Cucumis sativus L.) - Rasmi Krishnan V (Department of Agronomy, College of Horticulture, 2014)
A study on “ Nutrient management in organic farming of cucumber (Cucumis sativus L.) was carried out in the Department of Agronomy, College of Horticulture, Vellanikkara during 2012-2013. The experiment consisted of 13 treatments including different combinations of organic manures and supplements, package of practices recommendation by KAU, inorganics alone and control to develop a nutrient management strategy in organic farming of cucumber. The variety AAUC-2 was used for the study. The organic manures viz., FYM, poultry manure, vermi compost, neem cake and liquid organic manures viz., Beejamrutham, Jeevamrutham, Panchagavyam and fish amino acid were the sources of nutrients. All the treatments receiving FYM as basal dose along with seed treatment with azospirillum, phosphate solubilizing bacteria and Pseudomonas have shown early germination and seedling vigour. Growth parameters like length of vine, number of leaves, number of branches were significantly influenced by the treatments. The treatment receiving poultry manure + N P K recorded the maximum vine length on 45 DAS followed by poultry manure + Beejamrutham + Jeevamrutham + mulching. Highest number of leaves was produced by poultry manure +fish amino acid treated plants followed by poultry manure + panchagavyam treated ones. The number of branches was also significantly higher in poultry manure + fish amino acid treated plots. The LAI was significantly higher in poultry manure + panchagavyam treated plants. The flowering was early as 27 DAS in the treatment receiving poultry manure + fish amino acid against 38 days in N P K alone treatment and 47 days in the absolute control. The fruits could be harvested from the treatment receiving poultry manure + fish amino acid on 35 DAS followed by that receiving poultry manure + beejamrutham + jeevamrutham + mulching. Yield and yield attributes like number of fruits per plant, mean fruit weight were also significantly influenced by the application of different organic manures. Highest number of fruits/plant and weight of fruits were observed in Adhoc Package of practices. Highest yield of 53.94 t ha-1 was recorded in plots receiving Adhoc package of practices recommendations by KAU (Organic farming) which was 5.5 t more than the present package of practices recommendations by KAU. The total productive period of the crop was higher in organically treated plots. The period extended up to 98 days in the treatment receiving poultry manure + fish amino acid as against 77 days in N P K applied plots. The highest shelf life of 8.5 days was also recorded for the same treatment. With regard to the soil microbial count at different intervals of crop growth, the treatment receiving jeevamrutham and mulching resulted in the highest bacterial and fungal count where as the neem cake application resulted in the highest count of actinomycetes. All the micro organisms were minimum in the treatments receiving chemical fertilizers. Statistical analysis by Kendall’s test by ranks of the acceptability score revealed that there was significant variation among the treatments in the quality attributes of fruits. The highest score for appearance and colour was also recorded in the treatment receiving panchagavyam followed by the one receiving fish amino acid. The overall acceptability was also more for the fruits from the organically treated plots. The treatment receiving Adhoc POP was found to be significantly superior to other treatments in getting higher gross income, net return and B:C ratio followed by the present POP.